2016
DOI: 10.1016/j.imr.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Rg3-enriched Korean Red Ginseng enhances blood pressure stability in spontaneously hypertensive rats

Abstract: BackgroundKorean Red Ginseng (Panax ginseng) has been shown to exert antihypertensive effects. In particular, ginsenoside Rg3 is thought to be a potent modulator of vascular function. The present study was performed to examine the antihypertensive efficacy of Korean Red Ginseng (KRG) extract and Rg3-enriched KRG (REKRG) extract.MethodsSpontaneously hypertensive rats (SHRs) and Wistar–Kyoto rats (WKYs) were divided into six groups (WKY control, WKY-KRG, WKY-REKRG, SHR control, SHR-KRG, and SHR-REKRG), and systo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 33 publications
(52 reference statements)
0
15
0
Order By: Relevance
“…Another study compared blood pressure and blood vessel wall thickness after Rg3 administration in male mice. Mice treated with Rg3 significantly reduced blood pressure and vascular wall thickness (Nagar et al, 2016). These results suggest that Rg3 can be used as one of the therapeutic agents.…”
Section: Hypertensionmentioning
confidence: 64%
See 2 more Smart Citations
“…Another study compared blood pressure and blood vessel wall thickness after Rg3 administration in male mice. Mice treated with Rg3 significantly reduced blood pressure and vascular wall thickness (Nagar et al, 2016). These results suggest that Rg3 can be used as one of the therapeutic agents.…”
Section: Hypertensionmentioning
confidence: 64%
“…Moreover, Rg3 inhibited skin photo-aging and aided the recovery of photo-induced skin damage. (Nagar et al, 2016) Rg3 is being studied for its effects on various diseases and symptoms. In the following section, we discuss the effects of Rg3 on metabolic syndrome and its therapeutic prospects.…”
Section: Ginsenoside Rg3mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, functional ingredients with pharmacological properties, such as herbs, essential oils, and ginseng, are being used to develop healthier recipes. The health-promoting effects of ginsengs are well established with respect to their antioxidative [ 9 ], anti-inflammatory [ 10 ], antihypertensive [ 11 ], hypolipidemic [ 12 ], anti-diabetic [ 13 ], and cancer preventive activities [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…19 In previous studies, we have shown that Rg3 improves vascular function through eNOS activation 20 and enhances blood pressure stability in spontaneously hypertensive rats (SHRs). 21 Hypertension is a major risk factor for a range of cardiovascular diseases. Therefore, the development of new antihypertensive drugs with established efficacy and safety is necessary to improve treatment regimens.…”
mentioning
confidence: 99%